GEORGIA: REGIONAL STABILITY IN THE TRANSFORMED INTERNATIONAL SYSTEM - ASANISHVILI, Pikria; TUKVADZE, Avtandil (CENTRAL ASIA AND THE CAUCASUS, 2005)
The end of the bi-polar world raised the questions of how the international system will function, and whether it will become multipolar or unipolar. Some members of the expert community believe that geopolitical rivalry in today’s multipolar world will be the only way to sort things out among the entities of geopolitics. The struggle for spheres of influence is growing fiercer. Some international factors are gaining importance, while the significance of others is waning. This was probably why Gernot Erler, a Bundestag deputy, has offered the highly thought-provoking idea that in the early 21st century we are witnessing the regression of political culture to the ideas of the 20th century. The proc-ess is gradually becoming irreversible: in the West and in the East, political decision-making depends on geopolitical and geostrategic projects to an extent which is fraught with rising tension.1 Many political decisions in the internation-al sphere is still rooted in realism; whereby state interests prevail over all other considerations. But it should be noted that many of the conceptions and approaches circulating in the world system have changed. In the 20th century, it was vitally important to place state interests above anything else since international contacts were limited and the coefficient of their mutual dependence low.Today, globalization is gradually pushing aside national ideologies. Against the background of the changing international system, when the international community and its institutions are gaining weight and states are growing more interdependent, it has become possible to realize common interests. This, in turn, pushed the regional security problem to the foreground. The old models of the Cold War period should be revised. Security as a social category has long be-come a liberal postulate along with democracy and human rights, even though Emma Rothschild of Great Britain has pointed out that politicians of various political affiliations, irrespective of their willingness or unwillingness to embrace liberal values, treat security with due attention. The security category presents equal problems for all, despite the fact that it is equally urgent for each and every country: it is hard to determine which security type is needed for countries and social groups and what should be done to achieve it.2The post-bipolar international system tends toward regional security complexes for the simple reason that the capitalism/ socialism ideological confrontation no longer interferes with the functioning of regional sub-systems. Today, while regional and sub-regional systems are gradually coming into being, the process sometimes assumes sharp forms. The international system is seeking roads leading to a secure political and social milieu and complexes which can add stability to security. Today, the Eurasian zone is the main area of international relations; according to Zbigniew Brzezinski, it should acquire a Trans-Eurasian Security System (TESS).3 History knows of several regional stability and security models: the Holy Alliance formed in 1815 based on the primacy of super-regional power expected to consolidate other much weaker countries; and the collective security system which emerged after World War II when the West and the Soviet Union found themselves in two hostile camps. This gave rise to NATO and the Warsaw Treaty Organization (WTO) as collective security models. Under the latter model, states are fully aware of the real or associated enemy to be stopped by concerted military efforts. The entire model hinges on the idea of a common enemy, therefore it is better suited to rebuff it and deal with international problems rather than with regional socioeconomic issues. Then we see a collective security model designed to address region-al problems by means of negotiations within international legal principles, rather than through the use of force. It also envisages a collective response to aggression against one of its members. According to A. Malgin, a system which is too loose at the global level is best suited to the regional lev-el. In his article “Sredizemnomorskoe izmerenie evropeyskoy bezopasnosti” (the European Security Mediterranean Dimension), he used the OSCE to demonstrate that it is successfully coping with the tasks posed by its founders. Not limited to the military sphere, it is dealing with the humanitarian, economic, and political baskets.The changing international system has posed the problem of choosing a regional security model; by the same token it has confronted the South-ern Caucasus (and Georgia as its part) with the need to identify its place in it. The correct choice is critically important: the region is developing into a zone of rivalry among the superpowers. The local states, including Georgia, should clearly identify their positions in Eurasia; they should take into account the current and future processes in which the strong states are playing first fiddle. Georgia’s position is vitally important in terms of the regional security system it will choose, even though for political and economic reasons it carries little weight in the international system. The positions of strong states and their geostrategic and geopolitical interests in Georgia and the Southern Caucasus are much more consequential.